A case for corpus stylistics: Ian Fleming’s Casino Royale - Mahlberg, Michaela; McIntyre, Dan (John Benjamins Publishing, 2011)
In this article we investigate keywords and key semantic domains in Fleming’s Casino Royale. We identify groups of keywords that describe elements of the fictional world such as characters and settings as well as thematic signals. The keyword groups fall into two broad categories that are characterized as text-centred and reader-centred, with the latter providing particular clues for interpretation. We also compare the manually identified keyword groups with key semantic domains that are based on automatic semantic analysis. The comparison shows, for instance, how words that do not seem to fit a semantic domain can be seen as reader-centred keywords fulfilling specific textual functions. By linking our analysis to arguments in literary criticism, we show how quantitative and qualitative approaches can usefully complement one another.